Antimicrobial and iNOS inhibitory activities of the endophytic fungi isolated from the mangrove plant Acanthus ilicifolius var. xiamenensis - Chi, Wei-Chiung (Bot Stud, 2019)
BACKGROUND: Acanthus ilicifolius var. xiamenensis (Acanthaceae) is an old world mangrove species and has long been used as a folk remedy for treating various ailments in traditional medicine. The nature source of A. ilicifolius var. xiamenensis is now in short supply because of the urban development and habitat destruction. To better utilize this resource, biodiversity and bioactivity of endophytic fungi isolated from A. ilicifolius var. xiamenensis were investigated. RESULTS: A total of 168 fungal isolates were cultured from leaves and stems of the mangrove plant collected in January (winter) and July (summer) 2014 at Kinmen County, Taiwan. Spent culture extract of 28 isolates were found to have bioactivities against one of the following pathogenic microorganisms: the bacteria Bacillus subtilis, Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative) and the fungi Candida albicans and Cryptococcus neoformans. These positive extracts were mostly active against the Gram-positive bacteria and C. albicans. Corynespora cassiicola NTOU4889 and Xylaria sp. NTOU4900 inhibited growth of all 3 test bacteria whereas Phellinus noxius NTOU4917 inhibited both test fungi. A further anti-inflammatory study of culture extracts of these 28 isolates revealed that extracts with a high iNOS inhibition caused a low viability of cells, and those with a low iNOS inhibition had a high cell viability. Three extracts showed low cytotoxicity (i.e. > 100% cell viability) and high iNOS inhibition (< 15% of NO production) of cells and they were Phoma sp. 2 NTOU4338, Nodulisporium sp. NTOU4868 and Guignardia sp. NTOU4871. CONCLUSION: These results indicate that the endophytic fungi associated with A. ilicifolius var. xiamenensis can be a potential source of novel natural active substance.